APLIKASI WEB SISTEM INFORMASI SUNGAI DAN PANTAI (SISPA) UNTUK PENGELOLAAN SUMBERDAYA AIR - Wahjono, Heru Dwi (Center for Environmental Technology, 2015)
Development activity has been exploiting water resources (SDA) massively. Every year the number of critical watershed along with the increasing environmental degradation. Management of water resources are always either continued effort by the government to reduce the negative impact of environmental pollution. One way is to build an Information System Web-Based Coastal Rivers and can be used to determine the condition of water resources in the basin, so that the status of potential and water quality can be monitored at any time either by the government or the wider community and other civil society organizations . The information system Web-Based Coastal Rivers and can be realized by performing a data management of water resources in the basin structured through the development of Water Resource Database (DBSDA). Rivers and Coastal Information System (SISPA) Web-based was developed to assist the Ministry of Public Works in order to carry out the data management of water resources and coastal rivers in the basin in accordance with the rules established by the existing regulations, particularly the Law 7 Year 2004 on SDA and PP 42 Year 2008 on Management of Natural Resources.Ã‚Â Keywords : River and Coastal Information System, Water Resources Information SYstem, River Basin, River Basin Unit, DAS, SWS.